(3JMbjb GdNdGa aj CUMGH GdCYQGas - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s ((3CMeO Hf eUWai Hf jhSa Hf jMji Hf jhSa GdebOSi GdMfHdi s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdYOd hGdEfUGa CeG HYO ajbhd GdabjQ eQYi Hf jhSa GdMfHdi GdebOSi bO ESJNQJ Gddg SHMGfg ai JdNjU aQGFO hahGFO ZQQ JJYdb HGdcdGe Ydi CUMGH GdCYQGa s
(3BNQgG (B:s
(3aJCed hGdcdGe Ydi gPg GdBjI GdTQjaI eeG jWhd hajeG PcQfGg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B23s
(3HgG fXGe GdJYbjHIs
(3HBNQg fbhd eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B265s
Keywords: (3Gdabg GdMfHdjs